Sacred heritage : monastic archaeology, identities, beliefs - Gilchrist, Roberta (Cambridge : Cambridge University Press, 2020)
Roberta Gilchrist critically evaluates the concept of sacred heritage. Drawing on global perspectives from heritage studies, archaeology, museology, anthropology and architectural history, she examines the multiple values of medieval Christian heritage. Gilchrist investigates monastic archaeology through the lens of the material study of religion and reveals the sensory experience of religion through case studies including Glastonbury Abbey and Scottish monasticism. Her work offers new insights into medieval identity and regional distinctiveness, healing and magic, and memory practices in the sacred landscape. It also reflects on the significance of medieval sacred landscapes as contested heritage sites which hold diverse meanings to contemporary groups. This title is also available as Open Access.
Sacred values : medieval archaeology and spiritual heritage -- Monastic archaeology and national identity : the Scottish monastic experience -- Spirit, mind and body : the archaeology of monastic healing -- The materiality of magic : the ritual lives of people and things -- Monastic legacies : memory and the biography of place -- Sacred myths : archaeology and authenticity.
Title from publisher's bibliographic system (viewed on 20 Dec 2019).
Keywords: Christian antiquities -- Scotland; Archaeology, Medieval -- Scotland; Monasticism and religious orders -- History -- Middle Ages, 600-1500.; Archaeology and religion -- Case studies; Sacred space -- Conservation and restoration -- Case studies; Material culture -- Religious aspects -- Case studies